Health staff experiences with the implementation of early essential newborn care guidelines in Da Nang municipality and Quang Nam province in Viet Nam - Marianne S. Morseth; Tuan T. Nguyen; Malene Skui; Laura Terragni; Quang V. Ngo; Ha T. T. Vu; Roger Mathisen; Sigrun Henjum (BMC, 2020)
Abstract Background The World Health Organization (WHO) recommends early essential newborn care (EENC) - The First Embrace - as a simple lifesaving procedure for newborns. The successful implementation of EENC at scale requires an understanding of health staff experiences, including facilitators, barriers, and local adaptations of EENC. This study aims to gain insight into health staff experiences with implementation of EENC guidelines after participation in training and coaching initiatives in Da Nang municipality and Quang Nam province in Viet Nam. Methods In each province/municipality, we randomly selected one hospital from the following categories: public provincial/municipal hospital, public district hospital, and private hospital. We conducted in-depth interviews with 19 hospital staff (11 midwives, 5 doctors and 3 health managers) and two trainers during 7 days between September and October 2017. We used deductive/inductive thematic analysis to generate themes. Results The health staff reported improved staff and mother satisfaction, and health benefits for both mothers and newborns after implementing EENC. Facilitators to successful implementation were management support for resource allocation and collaboration across departments, and creative demand generation. Barriers included staff shortage, skepticism about the new protocols and practices and challenges translating knowledge and skills from trainings and coaching into practice. Conclusions After implementing EENC, through training and coaching using the WHO approach, health staff reported improved staff and mother satisfaction as well as health benefits for both mothers and newborns. An approach to develop competencies, with a focus on practical training and coaching, should be promoted to form, reinforce and sustain recommended EENC practices among health staff.